Effect of non-adherence to ARV therapy on 3-year life of HIV/AIDS patients: a cohort retrospective study - Hendra Dhermawan Sitanggang; Tri Yunis Miko Wahyono; Ira Marti Ayu (Riset Informasi Kesehatan, 2023)
Background: Antiretroviral drug Therapy (ART) has dramatically reduced the morbidity and mortality of People Living with HIV/AIDS (PLWHA). However, adherence to antiretroviral therapy has become a challenge due to a lifetime of therapy. Adherence to antiretroviral therapy is one determining factor in the success of treatment. Method: This study aimed to determine the influence of medication non-adherence on the 3-year survival of patients with HIV/AIDS. The study design used a retrospective cohort and calculated survival estimates using Cox regression. All HIV/AIDS patients in the RSPI-SS from 2010 – April 2012, totaling 164 patients, were obtained from medical records, a summary of treatment and ART (follow-up), pharmacy data, and ARV therapy monitoring books at the RSPI-SS. Data analysis using cox regression. Results: The cumulative survival probability of patients with HIV/AIDS at RSPI Prof. dr. Sulianti Saroso in the second year (24th month) was 95.6% and in the third year (in the 36th) was 91%. Multivariate analysis with Cox regression showed the factors that affected the 3-year survival of patients with HIV/AIDS are non-adherence to ART after being controlled by initial CD4 count (aHR = 7.608; 95% CI: 1.664 to 34.790) and non-compliance appointments after controlled by opportunistic infection, age and initial CD4 count (aHR = 2.456; 95% CI: 0.802 to 7.518). Among patients' non-adherence to ART, non-compliance appointments affected the 3-year survival of patients with HIV/AIDS after controlled by initial CD4 count, sex, CPT, modes of HIV transmission, WHO clinical stage, opportunistic infection, and age (aHR = 4.517; 95%CI: 0.729 to 27.987). Conclusion: Non-adherence to ART may cause a failure to suppress HIV viral, thus increasing the possibility of HIV mutations that can lead to drug-resistant and ultimately increase the risk of death. Patients who do not adhere to medication and do not adhere to their medication appointments show a higher risk of dying than those who adhere to HIV/AIDS. Non-adherence to taking medication in the first year can be used as a marker to monitor medication adherence and the patient's health condition in the future. Therefore, it is essential to monitor adherence to taking the medication regularly through ARV therapy surveillance activities.